ҲАМЗА ҲӘКИМЗАДА НИЯЗИЙДИҢ ТӘЛИМ-ТӘРБИЯЛЫҚ ОЙ-ПИКИРЛЕРИ - Сейтмуратов, Қ. (FAN va JAMIYAT, 2024)
The article discusses the educational-pedagogical activities and educational views of the great pedagogue H.H. Niyazi.